An Ethnographic Study of Didong: Body Music and the Enculturation of Gayo Children - Albayan, Amris; Sunarto, Bambang; Soewarlan, Santosa; Mistortoify, Zulkarnain; Puspa Juwita, Rani (JURNAL PENDIDIKAN USIA DINI, 2026)
This study aims to investigate the practice of Didong as a form of body music and its role in the enculturation process of Gayo children in Central Aceh Regency, Indonesia. It focuses on informal social spaces where children play with their peers. To analyze how body-based Didong becomes a medium of enculturation through musical experiences and spontaneous social interactions, an ethnographic-based qualitative approach is used. Data were collected through participatory observation and informal dialogue with children aged 5-10 years who practice Didong. The results reveal that rhythmic elements such as tepok tulu, tingkah, and geretek are produced through the technique of clapping both palms together in a collectively organized manner. Through peer imitation mechanisms, children can reproduce musical patterns, which internalize the Gayo cultural identity in an embodied way. Theoretically, this study contributes by deconstructing the understanding of traditional music from merely a formal performance into an autonomous system of enculturation in children's daily lives. These findings confirm that body music functions as a crucial informal pedagogical space for the sustainability of local traditions outside formal educational institutions.